2021
DOI: 10.22606/pra.2021.31002
|View full text |Cite
|
Sign up to set email alerts
|

Can Social Desirability Be Detected Statistically at the Macro-Sociological Level?

Abstract: While a few have argued that social science has been subject to progressive biases, others have discounted such ideas. However, no one has yet performed empirical tests over a large range of studies for such possible bias, which we label macro-level social desirability (MLSD). Combining the results from fifty-nine empirical studies that assessed rates of nonheterosexuality among children of same-sex parents, we found that the higher the maximum rates reported, the less likely those reports were to have been ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Social desirability response bias (Regnerus 2020) is another concept that is seldom considered as a possible factor in how people might respond to questions about human sexuality. Sometimes social desirability is measured but then apparently not used in an article’s statistical analyses (Lefevor et al 2020; Schumm 2015; Schumm and Crawford 2021a).…”
Section: Weak Social Science Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Social desirability response bias (Regnerus 2020) is another concept that is seldom considered as a possible factor in how people might respond to questions about human sexuality. Sometimes social desirability is measured but then apparently not used in an article’s statistical analyses (Lefevor et al 2020; Schumm 2015; Schumm and Crawford 2021a).…”
Section: Weak Social Science Theoriesmentioning
confidence: 99%
“…Even the minority of reviews that presented some contrary data usually cited only one or two studies to that effect. Yet, there is evidence from dozens of studies, summarized elsewhere, including meta-analyses (Schumm 2013, 2015, 2018, 2020c; Schumm and Crawford 2021a, 2021b; 2021c), that there the children of same-sex parents are more likely to become nonheterosexual. As a most recent example, Gartrell et al (2019) found that over 70% of the daughters of lesbian mothers (when the daughters were 25 years old, having been studied since birth in a longitudinal study) reported same-sex sexual attractions.…”
Section: Confirmation Bias In Social Sciencementioning
confidence: 99%